2021
DOI: 10.1038/s41371-021-00610-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure levels among children in rural Uganda: results from 1913 children in a general population survey

Abstract: Despite increasing levels of adult hypertension in sub-Saharan Africa (SSA), there is limited information on elevated blood pressure among children in SSA. We described the distribution of blood pressure among children in rural Uganda and estimated hypertension prevalence. We conducted a cross-sectional study in south-western Uganda, collecting demographic, anthropometric and blood pressure measurements from children aged 6-12 years. Children with elevated blood pressure (systolic and/or diastolic blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…A high statistical significance was found between BMI and pre-HTN and HTN Gewa et al [ 39 ] Kenya 390 10–12 Overweight (BMI-for-age percentiles) children with EBP was 1.85-fold greater and the proportion of children with HTN was 1.83-fold greater compared with normal weight children. Similar patterns of significant associations were seen among obese children, those with central obesity and those with high total skinfold values Kansiime et al [ 40 ] Uganda 1913 6–12 Higher BMI associated with higher BP. Obesity was largely irrelevant in this study Physical activity Jourbet et al [ 41 ] South Africa 1009 8–13 39% physically inactive (self-reported) Hypertensive children were more likely to be overweight/obese, but only if they did not meet physical activity recommendations Fossou et al [ 42 ] Ivory Coast 1251 5–15 8.1% of overweight/obese (10.3% (BMI z-score > + 1SD WHO)) children do not play sport (self-reported) BMI influenced SBP and DBP in both sexes.…”
Section: Childhood Hypertension In Africasupporting
confidence: 60%
See 1 more Smart Citation
“…A high statistical significance was found between BMI and pre-HTN and HTN Gewa et al [ 39 ] Kenya 390 10–12 Overweight (BMI-for-age percentiles) children with EBP was 1.85-fold greater and the proportion of children with HTN was 1.83-fold greater compared with normal weight children. Similar patterns of significant associations were seen among obese children, those with central obesity and those with high total skinfold values Kansiime et al [ 40 ] Uganda 1913 6–12 Higher BMI associated with higher BP. Obesity was largely irrelevant in this study Physical activity Jourbet et al [ 41 ] South Africa 1009 8–13 39% physically inactive (self-reported) Hypertensive children were more likely to be overweight/obese, but only if they did not meet physical activity recommendations Fossou et al [ 42 ] Ivory Coast 1251 5–15 8.1% of overweight/obese (10.3% (BMI z-score > + 1SD WHO)) children do not play sport (self-reported) BMI influenced SBP and DBP in both sexes.…”
Section: Childhood Hypertension In Africasupporting
confidence: 60%
“…These factors have been reported in children and adolescents between the ages of 1–19 years, with the majority of the studies done in Western and Southern African regions. Among the BP associated risk factors, the majority of the findings showed an adverse association between overweight/obesity and pre-hypertension and/or hypertension [ 27 ••, 28 ••, 29 40 ]. The prevalence of overweight/obesity ranged from 2.2 to 33.0% with the highest prevalence being reported in South Africa.…”
Section: Childhood Hypertension In Africamentioning
confidence: 99%
“…A study conducted among high school children in Uganda found that 11% of the 688 children had elevated blood pressure [ 5 ]. Another study in rural Uganda among 1913 children found 44.2% had elevated blood pressure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%